Political Silence of Youth in Togo Mobile Phones, Information and Civic (dis)Engagement - Keja, Roos (Connectivity and Society in Africa, 2022)
In the constrained socio-cultural, economic and political context of Sokodé, Central Togo, social hierarchies and distrust are defining factors for the intimacy of information. Towards this background, this book explores the usages and roles of mobile phones in everyday life in Sokodé, and links this to civic engagement. It shows that mobile phones do not necessarily lead to increased civic-ness, yet they do provide a sense of possibility.